Preliminary Study: Study of Supporting Facilities for Natural Science Mini Project Practicum Models of Junior High Schools in Mataram - Ardiansyah, Bakhtiar; Ramdani, Agus; Hakim, Aliefman; Makhrus, Muh (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This study aims to describe the supporting facilities for the Natural Science Mini Project Practicum (PIMPA) model of learning from the availability of tools and chemicals as well as books or literature available in SMP throughout Mataram City. This research was conducted in three schools spread outside the urban areas of Mataram City, especially those located close to the tourism area of Mataram City, namely: SMPN 11 Mataram, SMPN 17 Mataram, and SMPN 21 Mataram. The research subjects were laboratories and libraries, and the research objects were laboratory support facilities. The form of activity carried out is the recording of documents (inventory) of laboratory equipment and their use in science practicum activities. The data from this study were analyzed descriptively qualitatively. The results of this study indicate that the laboratory carrying capacity in the PIMPA model is the availability of laboratory equipment for science practicum activities at SMPN 11 Mataram is 77.27% (adequate); SMPN 17 Mataram available 77.27% (adequate); and SMPN 21 Mataram available 72.72% (adequate).Â